The Monocytes That Repopulate in Mice After Cyclophosphamide Treatment Acquire a Neutrophil Precursor Gene Signature and Immunosuppressive Activity - Ding, Zhi-Chun; Aboelella, Nada S.; Bryan, Locke; Shi, Huidong; Zhou, Gang (Frontiers in Immunology, 2021)
Cyclophosphamide (CTX) is a major component of the chemotherapy conditioning regimens used in the clinic to prepare cancer patients for hematopoietic stem cell transplantation or adoptive T cell therapy. Previous studies have shown that CTX given at nonmyeloablative doses in mice and patients leads to expansion of myeloid cells within which the monocytic subset exhibits immunosuppressive activity. However, the ontogeny and gene expression signature of these CTX-induced monocytes are not well-defined. Here we report that the expansion of myeloid cells is a default process intrinsic to hematopoietic recovery after chemotherapy. During this process, the monocytes repopulated in mice acquire immunosuppressive activity which can persist long after cessation of chemotherapy. Moreover, monocytes acquire a gene signature characteristic of neutrophil precursors, marked by increased proliferative capability and elevated expressions of multiple primary and secondary granules. We provide evidence that CTX-induced myeloid cell expansion is regulated by DNA methyltransferase 1 (Dnmt1) and dependent on chemotherapy-induced microbial translocation. These findings help advance our understanding of the differentiation, heterogeneity, and function of myeloid cells repopulating after chemotherapy.